Exploring the relationship between cognition and functional verbal reasoning in adults with severe traumatic brain injury at six months post injury. (21st March 2017) - Avramović, Petra; Kenny, Belinda; Power, Emma; McDonald, Skye; Tate, Robyn; Hunt, Louise; MacDonald, Sheila; Heard, Rob; Togher, Leanne
ABSTRACT: Objective(s) : This study aims to determine the association between cognitive impairment and functional verbal reasoning in adults with severe traumatic brain injury (TBI), at six months post-injury. Method(s) : 38 participants with severe TBI were assessed using the four tasks on the Functional Assessment of Verbal Reasoning and Executive Strategies (FAVRES) [1] and a battery of neuropsychological tests at 6 months post injury in a cross-sectional observational study. Results : Overall performance on the FAVRES [1] was strongly associated with overall performance on the neuropsychological battery (rho = 0.60). FAVRES Task 2 and FAVRES Task 4 had the most significant positive associations with the cognitive indices of Attention and speed of processing, Memory and Executive functions. There was one weak significant association between the Task 1 Accuracy score and the Total Cognitive index (rho = 0.46). Conclusions : Performance on the FAVRES [1] is positively associated with cognitive processes. Participants with stronger verbal reasoning skills which may be required for activities in work, home and social contexts also had higher scores on tests of cognitive functioning. These findings may inform clinical practices for speech pathologists and other health professionals, in the assessment and treatment of cognitive communication disorders during early stages of recovery in people with severe TBI.